Mechanical and Thermal Properties of 3D‐Printed Biocomposites of Polylactic Acid and Thermally Modified Wood Flour with Silver Nanoparticles - Elif Yurttas; Nadir Ayrilmis (Macromolecular Materials and Engineering, 2023)
Abstract This study investigates the effects of thermal treatment and silver nanoparticles on the mechanical and thermal properties of additively manufactured wood/polylactic acid (PLA) specimens. The 5 and 10 wt% additions of the wood flour into the PLA matrix are done in the twin screw extruder. The test specimens are produced from the filaments with a diameter of 1.75 mm using 3D printer. The mechanical properties of the 3D‐printed wood/PLA specimens are affected by the wood flour content, thermal treatment of wood, and silver nanoparticles. The 3D‐printed neat PLA specimens have better mechanical properties than the wood flour‐filled PLA specimens. The bending strength of the specimens enhances with increasing wood flour content while the tensile strength decreases. The increases in the mechanical properties reveal that the thermal treatment of the wood improves the compatibility between wood and PLA matrix, which hereby improves the interfacial adhesion. The addition of the silver nanoparticles positively affects the mechanical properties and it is more compatible with thermally modified wood particles as compared to the untreated wood particles.